Integrating environmental considerations into the agricultural policy process: Evidence from Nigeria - Babu, Suresh Chandra; Mavrotas, George; Prasai, Nilam (International Food Policy Research Institute, 2017)
Policy processes that design, develop, and implement sectoral policies often leave environmental considerations to a central environmental authority. As a result, the environmental implications and consequences of policies and programs, even when they are explicitly recognized as a part of the policies’ mandate, are often ignored at the time of implementation. This paper shows how individual, organizational, and systemic factors that enhance the abilities of policy actors are crucial for better integration of environmental considerations in policy processes. Using data collected in Nigeria, we develop empirical evidence on such factors so that the sectoral policy process can be improved for better environmental outcomes. The results indicate that explicit identification of environmental challenges, better collaboration and communication between researchers and policy makers, and a combination of the expertise of young analysts with the experience of senior policy makers can improve explicit consideration and follow-up of environmental issues in sectoral policy processes. The lessons from this paper are also applicable to the environmental considerations of the Agriculture Promotion Policy, the current policy road map for promotion of the agriculture sector in Nigeria, and to other developing countries’ attempts to implement such sectoral policies.